FORECASTING VOLCANIC EVENTS: SOME CONTEMPORARY ISSUES - McGuire W.J.; Kilburn C.R.J. (My University, 1997)
As the regions around active volcanoes succumb to large increases in population, particularly in the developing world where most of the high-risk volcanoes are located, the threat posed by eruptions becomes increasingly serious. Improvements in eruption forecasting are critical to combat this situation, for reducing injury and loss of life, and for minimizing the detrimental effects to local economies and to the fabric of society. Better-constrained forecasts are strongly dependent on geophysical and other data gathered during a program of volcano surveillance, and we reveal how, if interpreted in terms of static rock fracturing, analysis of changes in volcanic seismicity and ground deformation may be used to forecast more accurately the onset of eruptive activity. As illustrated by recent events at several volcanoes, studies of previous activity, increased levels of monitoring, and improved training of scientists are also all crucial to improving forecasts of impending eruptions.